Evaluation of the Industrial Work Practice Program (PRAKERIN) Curriculum at SMKN 1 Lembah Melitang, West Pasaman District Using the CIPP Model - Aisatun Nadroh; Irja Eka Putri; Khaironita Khaironita; Fildya Rizki; Liza Efriyanti (YASIN, 2026)
The implementation of vocational internship curricula requires systematic evaluation to ensure alignment between school-based learning and labour-market demands. This study evaluates the implementation of the Industrial Work Practice Program (Prakerin) curriculum at SMKN 1 Lembah Melintang, West Pasaman Regency, using Stufflebeam’s Context, Input, Process, and Product (CIPP) model. A quantitative descriptive-evaluative design was employed, involving purposively selected participants comprising 99 students, 20 supervising teachers, one principal, and six business and industry representatives. Data were collected using a CIPP-based questionnaire with a 4-point Likert scale, supported by documentation and field observation. The scores for each CIPP dimension were converted into percentages and categorized. The results indicate that the overall implementation of Prakerin was positive, with the context dimension reaching 78.82% (good), input 74.20% (good), process 74.01% (good), and product 73.45% (good). Stakeholder-based analysis showed that tutors and the principal provided relatively higher ratings, ranging from very good to good, whereas industry representatives and students reported lower perceptions in several areas. These findings indicate that Prakerin aligns with vocational education objectives and supports the development of students’ technical competencies and work readiness. However, persistent gaps remain in soft skills, particularly communication, discipline, and adaptability, as well as in coordination between schools and industry partners. The study recommends strengthening formal school–industry agreements through shared competency standards, enhancing pre-internship soft-skills preparation, establishing integrated monitoring and evaluation mechanisms, and conducting regular facility audits and mentor training. This study contributes to vocational curriculum evaluation by demonstrating the usefulness of the CIPP model in identifying implementation strengths and gaps, with implications for improving technical and vocational education and training policy and optimizing Prakerin as a bridge between vocational schooling and the labour market.